2022
DOI: 10.1021/jacs.2c00825
|View full text |Cite
|
Sign up to set email alerts
|

The Sensitivity of Metal Oxide Electrocatalysis to Bulk Hydrogen Intercalation: Hydrogen Evolution on Tungsten Oxide

Abstract: Metal oxides are attracting increased attention as electrocatalysts owing to their affordability, tunability, and reactivity. However, these materials can undergo significant chemical changes under reaction conditions, presenting challenges for characterization and optimization. Herein, we combine experimental and computational methods to demonstrate that bulk hydrogen intercalation governs the activity of tungsten trioxide (WO 3 ) toward the hydrogen evolution reaction (HER). In contrast to the focus on surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 69 publications
2
42
0
Order By: Relevance
“…[ 27 ] More recently, the Augustyn and Mpourmpakis/McKone groups have both suggested that protons inserted into WO 3 govern the reactivity toward the hydrogen evolution reaction. [ 28,29 ] All these elements reinforce the idea that there is a crucial need to elucidate the key factors governing PICET reactions, and more specifically in aqueous unbuffered media. This is of prime interest for the development/optimization of not only water‐based electrochemical charge storage devices, but also of many water‐based energy conversion systems.…”
Section: Introductionmentioning
confidence: 67%
“…[ 27 ] More recently, the Augustyn and Mpourmpakis/McKone groups have both suggested that protons inserted into WO 3 govern the reactivity toward the hydrogen evolution reaction. [ 28,29 ] All these elements reinforce the idea that there is a crucial need to elucidate the key factors governing PICET reactions, and more specifically in aqueous unbuffered media. This is of prime interest for the development/optimization of not only water‐based electrochemical charge storage devices, but also of many water‐based energy conversion systems.…”
Section: Introductionmentioning
confidence: 67%
“…The linear Poisson–Boltzmann implicit solvation model as implemented in VASPsol with a Debye screening length of 3.0 Å was utilized to simulate water (dielectric constant = 78.4) and the electrolyte and maintain the neutrality of the simulation cell . The details regarding how to correct the electronic energy due to an electron being added to or removed from the system and how to construct free energy surfaces can be found in the Supporting Information (SI) or our previous works. , This approach has been used by our group , and others to study a variety of electrochemical reactions. Some recent theoretical studies have suggested that better thermodynamics of overall electrochemical reactions can be achieved by correcting the computed free energies of the gas molecules involved in the reactions. We found that applying the correction suggested by Calle-Vallejo and co-workers to CO 2 , which is the only molecule in the current system, leads to no change in our major conclusions (Table S2).…”
Section: Computational Detailsmentioning
confidence: 99%
“…Nano-metal oxide catalysts offering intriguing properties and stability, and low price are the subject of intense investigation, particularly in the energy and environment-related catalysis eld. [1][2][3][4] However, some nano-metal oxides, like TiO 2 , CeO 2 , and ZrO 2 , suffer from poor catalytic efficiency due to their low electron transfer rates and limited active sites, greatly restricting their application. [5][6][7][8] To this end, manufacturing oxygen vacancies (OVs) on them is a simple and convenient way to enhance their intrinsic catalytic properties, which aroused tremendous interest.…”
Section: Introductionmentioning
confidence: 99%